An analysis and evaluation of test and item bias in the prediction context. - Humphreys, Lloyd G. (Journal of Applied Psychology, 1986)
Prediction des evaluations professionnelles biaisees (specialement aux tests d'aptitude) par des considerations d'appartenance a une minorite nationale, ethnique ou raciale